2014
DOI: 10.1007/s00438-014-0872-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the WRKY gene family in cotton

Abstract: WRKY proteins are major transcription factors involved in regulating plant growth and development. Although many studies have focused on the functional identification of WRKY genes, our knowledge concerning many areas of WRKY gene biology is limited. For example, in cotton, the phylogenetic characteristics, global expression patterns, molecular mechanisms regulating expression, and target genes/pathways of WRKY genes are poorly characterized. Therefore, in this study, we present a genome-wide analysis of the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 65 publications
7
115
0
1
Order By: Relevance
“…Most SiWRKY genes were highly expressed in roots, whereas a few SiWRKY genes were expressed in developing seeds. This is consistent with observations made in other plants, including rice [18], cucumber [33], grape [42], apple [13], cassava [30], cotton [43], physic nut [41], and cabbage [44]. Our results revealed that SiWRKY genes are expressed tissuespecifically and the high expression levels observed in roots might reflect their roles in responses to abiotic and biotic stresses that first affect plants below ground.…”
Section: Diverse Expression Patterns Of Siwrky Genes In Different Tissupporting
confidence: 92%
“…Most SiWRKY genes were highly expressed in roots, whereas a few SiWRKY genes were expressed in developing seeds. This is consistent with observations made in other plants, including rice [18], cucumber [33], grape [42], apple [13], cassava [30], cotton [43], physic nut [41], and cabbage [44]. Our results revealed that SiWRKY genes are expressed tissuespecifically and the high expression levels observed in roots might reflect their roles in responses to abiotic and biotic stresses that first affect plants below ground.…”
Section: Diverse Expression Patterns Of Siwrky Genes In Different Tissupporting
confidence: 92%
“…NAC transcription factors; Shang et al, 2013) or by a combination of segmental duplications (SDs) and tandem duplications (TDs; e.g. WRKY transcription factors; Dou et al, 2014). For apple (most recent WDG after the divergence for peach [Prunus persica] according to Verde et al [2013]), a recent study on nucleotide-binding site LRR genes showed that they also stem mostly from SDs and TDs (Arya et al, 2014).…”
Section: Subgroup-and Species-specific Expansionsmentioning
confidence: 99%
“…A large number of WRKY genes have been isolated and characterized in various plant species, such as in Arabidopsis (Eulgem et al, 2000), Zea mays (Wei et al, 2012), Gossypium (Dou et al, 2014), Medicago truncatula ( and Nan, 2014), Cucumis sativus (Ling et al, 2011), B. rapa , Vitis vinifera , Carica papaya (Pan and Jiang, 2014), Coffea arabica (Ramiro et al, 2010), Populus , Hevea brasiliensis , Coptis japonica (Kato et al, 2007), and Catharanthus roseus (Yang et al, 2013). However, knowledge on WRKYs of G. biloba remains limited.…”
Section: Discussionmentioning
confidence: 99%